High School and Beyond, 1980: Sophomore and Senior Cohort Second Follow-up (1984) ([Verlag nicht ermittelbar], 1985)
This data collection constitutes the third wave of data in the High School and Beyond series. The base-year data (ICPSR 7896) were collected in 1980, and the first follow-up (ICPSR 8297) was conducted in 1982. The series is a longitudinal study of students who were high school sophomores and seniors in 1980. As with the first follow-up, the structure and documentation of High School and Beyond Second Follow-Up data files represent a departure from base-year (1980) practices. While the base-year student file contains data from both the senior and sophomore cohorts, the two follow-up surveys provide separate student files for the two cohorts. Each of the cohort files for this collection merges the base year and first follow-up data with second follow-up data. Data collected for the sophomore cohort second follow-up differ substantially from data collected for the first follow-up since by 1984 the majority of respondents were out of high school and enrolled in postsecondary school, working, or looking for work. File 1, the Sophomore Cohort Second Follow-up Sample File, includes detailed questionnaire responses on background information, education, other training, military experience, work experience, periods unemployed, family information, income, experiences, and opinions. Information is also presented on the kind of school attended, hours per week spent in class, degree, certificate or diploma being sought, and requirements completed. Financial information in this file includes items on tuition and fees, scholarships, and financial aid from parents to the respondent and to any siblings. Work history data, including occupation, industry, gross starting salary, gross income, hours per week worked, and job satisfaction, are available along with data on the family, including the spouse's occupation and education, date of marriage(s), and number of children. File 5, the Senior Cohort Second Follow-up Sample File, repeats many of the same variables that are present in the first follow-up for this cohort. Respondents were asked to update background information, to provide information about postsecondary education, work experience, military service, family, income, and life goals. New items include a limited series on computer literacy (e.g., use of computers and software, knowledge of computer language), detailed information on financial assistance received from parents for pursuing postsecondary education, education and training outside of regular school, college or military programs (on-the-job and other employer-provided training), and periods of unemployment. Files 9,11,12, and 13 contain transcript data from each postsecondary institution reported by sample members of the High School and Beyond elder cohort (1980 senior cohort) in their responses to the High School and Beyond First Follow-up (1982) and Second Follow-up (1984) surveys. Data are available for several types of postsecondary institutions, ranging from short-term vocational or occupational programs through major universities with graduate programs and professional schools. Data in these four rectangular files--Student, Transcript, Term, and Course Files--are organized to be used in combination hierarchically. Information is available on terms of attendance, fields of study, specific courses taken, and grades and credits earned. A supplementary survey, the Administrator and Teacher Survey (ATS), was conducted in 1984 in approximately half of the schools sampled in the original High School and Beyond study. The ATS was designed to explore findings from research on effective schools, which were defined as those schools in which students perform at higher levels than would be expected from their backgrounds and other factors. The ATS provides measures of staff goals, school climates, and other processes identified in the effective schools literature as being important for achieving educational excellence. Separate questionnaires were administered to teachers, administrators, vocational education coordinators, and heads of guidance. Items in the questionnaires were selected to complement information already in the High School and Beyond database. Included were questions on staff goals, pedagogic practices, interpersonal relations of staff, work load of teachers, staff attitudes, availability and use of guidance services, planning processes, hiring practices, special programs, and linkages to local employers, parents, and the community.